The Difference Nothing Makes: Creatio Ex Nihilo, Resurrection, and Divine Gratuity - Robinette, Brian DuWayne (Theological studies, 2011)
In response to recent charges that creatio ex nihilo imposes a dubious metaphysics upon biblical theologies of creation, with the result that divine power is valorized at the expense of a creation in process, the author argues that such criticisms misrepresent the doctrine's logic that illuminates those biblical theologies while making explicit in philosophical terms the gratuitous and noncontrastive relationship between God and creation. Issues of power, evil, and forgiveness are discussed as the author analyzes the doctrine's logic and historical development.